Phase relations in Bi-rich part of the Bi-Ga-Ni system - Živković, Dragana; Manasijevic, Dragan; Balanovic, Ljubisa; Minic, Dusko; Cosovic, Vladan; Kostov, Ana; Zivkovic, Zivan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2012)
The results of phase relations investigation in bismuth-rich part of ternary Bi-Ga-Ni system are presented in this paper. Two sections with constant bismuth content equal to 80 and 90 at% were investigated experimentally using DSC and SEM-EDS methods and predicted thermodynamically by CALPHAD method. Calculated phase diagrams showed reasonable agreement with experimental data.